Veterinary aid clinic assessments of working ponies in West Nusa Tenggara province, Indonesia: A retrospective study - Drought, Amanda; Arifianto, Dinar; Voss, Jan T.; McLay, Sarah J.; Jabbar, Abdul; Hitchens, Peta L.; El-Hage, Charles M. (Austral Journal of Veterinary Sciences, 2023)
Working ponies in the West Nusa Tenggara (NTB) province of Indonesia are relied upon as the principal mode of transport. They have important cultural, logistical and One Health significance for the local community. Given the tropical climate, these ponies face well recognised health and welfare challenges . Parameters relating to the general health and welfare of the ponies were assessed following data analysis of clinical records from three veterinary clinics held in 2018 and 2019. Records relating to 454 clinical examinations of ponies (n=365 stallions) aged between 1 to 25 years (mean 7.59 ± 4.70) were analysed. The mean body condition score (1 to 5 scoring system) across all clinics was 2.89 (±0.49; range 1.5, 4.5), with no significant difference between clinics (P= 0.297). The majority of ponies (84.57%; 95% CI 80.50, 87.92; 307/363) assessed presented with tachypnoea, 37.24% presented with tachycardia (95% CI 32.78, 41.92; 159/427), 14.80% (95% CI 11.10, 19.46; 41/277) recorded rectal temperatures considered hyperthermic (>38.5°C), and 38.0% did not show obvious evidence of sweating (95% CI 32.21, 44.16; 95/250). Ponies examined at the April/May 2019 clinic were more likely to be considered hyperthermic (P=0.009) and/or presented with tachycardia (P<0.001), whereas ponies examined in the November 2019 clinic were more likely to present with tachypnoea (P=0.001). In general, the objective measures of body condition and health indices of these ponies were considered adequate. Some abnormalities relating to prolonged recovery following exercise whilst working were considered likely related to thermoregulatory stress. Parasite burdens were found to be low, no haemoprotozoan parasites were detected and median faecal egg count was zero. Measures to encourage cooling and greater frequent rest periods continued surveillance and monitoring the health of these ponies will result in both enhanced welfare and advances in One Health initiatives.